Evaluation of an instrument to measure teamwork in multidisciplinary critical care teams. Issue 3 (5th January 2011) - Weller, Jennifer; Frengley, Robert; Torrie, Jane; Shulruf, Boaz; Jolly, Brian; Hopley, Lara; Hendersdon, Kaylene; Dzendrowskyj, Peter; Yee, Bevan; Paul, Adam
Abstract : Introduction: Teamwork failures contribute to adverse events causing harm to patients. Establishing and maintaining a team and managing the tasks are active processes. Medical education largely ignores teamwork skills. However, lack of robust instruments to measure teamwork limits evaluation of interventions to improve it. The authors aimed to develop and validate an instrument to measure teamwork behaviours. Methods: From existing literature, the authors developed an instrument, gaining rater consensus that the final 23 items were comprehensive, comprehensible and observable. Data on the instrument were obtained from three expert raters who scored videotaped simulations of 40 critical care teams (one doctor, three nurses) participating in four simulated emergencies. Exploratory Factor Analysis, Generalisability Analysis and rater interviews on assessor performance provided information on the properties of the instrument. Results: Exploratory Factor Analysis found items clustered into three factors: Leadership and Team Coordination; Mutual Performance Monitoring; and Verbalising Situational Information. Internal consistencies (Cronbach's α) for these factors were 0.917, 0.915 and 0.893, respectively. The Generalisability coefficient for overall team behaviour was 0.78 and the G coefficients for the three factors were 0.85, 0.4 and 0.37, respectively. Variance Components and interview data provided insight into individual item performance. Significantly improved performance with time and seniority supported construct validity. Discussion: The instrument performed well as an overall measure of team behaviour and reflected three dimensions of teamwork. Triangulation of information on the instrument, the factors and individual items will allow a methodical and informed approach to further development of the instrument. The ultimate goal is an instrument that can robustly evaluate interventions to improve team function in healthcare.